Real-Time Surfactant-Free Emulsification of Plastic-Derived Diesel Oil: Combustion and Emission Characteristics - Prabowo, Wargiantoro; Yahya, Wira Jazair; Ithnin, Ahmad Muhsin; Sugeng, Dhani Avianto; Anggoro, Trisno; Saputro, Frendy Rian; Rosyadi, Erlan (Automotive Experiences, 2026)
Plastic waste pyrolysis has emerged as a promising strategy for converting non-recyclable plastics into plastic-derived diesel oil (PDDO), providing a pathway for both waste valorization and alternative fuel production. However, the direct utilization of PDDO in diesel engines remains constrained by suboptimal combustion behaviour and elevated exhaust emissions. While real-time non-surfactant emulsion fuel supply systems (RTES) have been widely investigated for conventional diesel fuels, their application to PDDO has not yet been systematically evaluated in engine operation. This study presents the first implementation of a real-time non-surfactant emulsification system to generate surfactant-free water-in-PDDO emulsions containing 5–15% water by volume. Engine performance and exhaust emissions were experimentally assessed using a 4.5 kW single-cylinder compression-ignition generator at low and high loads. The results indicate that controlled water addition modifies combustion behaviour by improving spray atomization and secondary droplet breakup associated with micro-explosion phenomena. Among the tested blends, the 15% water emulsion (EPO15) provided the most balanced performance, improving brake thermal efficiency by 6.48% while reducing NOx emissions by up to 47.06% compared with the baseline fuel. Exhaust gas temperature was consistently reduced, without substantial deterioration in fuel consumption. These findings demonstrate that RTES can enhance the combustion and emission characteristics of PDDO, supporting its potential application in small-scale compression ignition engine systems.